On a Model for the Storage of Files on a Hardware: Statistics at a Fixed Time and Asymptotic Regimes - Vincent Bansaye (Journal of Probability and Statistics)
We consider a version in continuous time of the parking problem of Knuth. Files arrive following a Poisson point process and are stored on a hardware identified with the real line, in the closest free portions at the right of the arrival location. We specify the distribution of the space of unoccupied locations at a fixed time and give asymptotic regimes when the hardware is becoming full.